The CEO pay slice - Bebchuk, Lucian A.; Cremers, K.J. Martijn; Peyer, Urs C. (Journal of Financial Economics, 2011)
We investigate the relation between the CEO Pay Slice (CPS)—the fraction of the aggregate compensation of the top-five executive team captured by the Chief Executive Officer—and the value, performance, and behavior of public firms. The CPS could reflect the relative importance of the CEO as well as the extent to which the CEO is able to extracts rents. We find that, controlling for all standard controls, CPS is negatively associated with firm value as measured by industry-adjusted Tobin's q. CPS also has a rich set of relations with firms' behavior and performance. In particular, CPS is correlated with lower (industry-adjusted) accounting profitability, lower stock returns accompanying acquisitions announced by the firm and higher likelihood of a negative stock return accompanying such announcements, higher odds of the CEO receiving a lucky option grant at the lowest price of the month, lower performance sensitivity of CEO turnover, and lower stock market returns accompanying the filing of proxy statements for periods when CPS increases. Taken together, our results are consistent with the hypothesis that higher CPS is associated with agency problems and indicate that CPS can provide a useful tool for studying the performance and behavior of firms.